2004
DOI: 10.1002/anie.200454125
|View full text |Cite
|
Sign up to set email alerts
|

Combined Spectroscopic and Theoretical Evidence for a Persistent End‐On Copper Superoxo Complex

Abstract: A tale of two modes: An end‐on copper superoxo complex was identified in a combined experimental and theoretical study. Theory clearly discloses the presence of an end‐on complex (see picture, O red, Cu pink, N green) with a minute isotopic resonance Raman splitting below experimental resolution. The results cast doubts on the uncritical use of 16O,18O isotopic‐labeling Raman experiments to discriminate end‐on from side‐on bonding modes in M(O2) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
139
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 49 publications
17
139
0
1
Order By: Relevance
“…3, 4, 5, and 6 unrestricted DFT level, the nitrogen atom of the triazacyclononane ring originally axially coordinated to copper decoordinates (although the nitrogen lone pair remains directed towards the copper atom); subsequent full optimization leads to a structure that maintains the side-on coordination mode for O 2 , 1 6 u (g 2 ), although the orientation of the O 2 fragment is rotated compared with that in 1 6 r (g 2 ). It is noteworthy that Schatz et al [26] observed exactly the same phenomenon in their DFT studies of 5: in order to go from g 1 to g 2 coordination, one nitrogen atom of the tris(tetramethylguanidino)tren ligand had to be permitted to decoordinate. Key geometric details for all structures of 6 are provided in Table 3.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…3, 4, 5, and 6 unrestricted DFT level, the nitrogen atom of the triazacyclononane ring originally axially coordinated to copper decoordinates (although the nitrogen lone pair remains directed towards the copper atom); subsequent full optimization leads to a structure that maintains the side-on coordination mode for O 2 , 1 6 u (g 2 ), although the orientation of the O 2 fragment is rotated compared with that in 1 6 r (g 2 ). It is noteworthy that Schatz et al [26] observed exactly the same phenomenon in their DFT studies of 5: in order to go from g 1 to g 2 coordination, one nitrogen atom of the tris(tetramethylguanidino)tren ligand had to be permitted to decoordinate. Key geometric details for all structures of 6 are provided in Table 3.…”
mentioning
confidence: 66%
“…With such rare examples of isotopomer peak splitting, an important question is whether such peak splitting or the absence thereof (i.e., the negative result) is sufficient to differentiate between g 1 and g 2 coordination modes. Schatz et al [26] recently faced this exact question for the case of a 1:1 Cu-O 2 adduct with a tris(tetramethylguanidino)tren ligand 5. The RR spectrum showed only a single absorption for the two mixed-label isotopomers, which might be interpreted to imply a side-on coordination mode.…”
Section: Introductionmentioning
confidence: 99%
“…Such species have been found in the reactions of O 2 with heme proteins and models (6,7) as well as with one copper enzyme (8) and several synthetic copper and nickel complexes (9)(10)(11)(12)(13)(14)(15)(16). Such species have also been invoked in the mechanisms for nonheme iron enzymes, but only indirect evidence has been obtained to date (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic evidence for an analogous formulation has also recently been reported for a copper enzyme peptidylglycine ␣-hydroxylating monooxygenase (PHM) (8). Furthermore, synthetic copper(I) and nickel(I) complexes react with O 2 to give rise to copper and nickel superoxo species (9)(10)(11)(12)(13)(14)(15)(16) 2 was prepared by using the same procedure in the presence of 10 eq of D 2 O. All manipulations with complex 1 and solutions thereof were carried out under inert atmosphere by using a glovebox filled with nitrogen.…”
mentioning
confidence: 99%
“…Compound 2 also has been established by X-ray crystallography to bind O 2 end-on, 32 and its ground electronic state has been confirmed to be a triplet. 35 Structure 2 was originally assigned, incorrectly, to have a singlet ground state, 20 based in part on density functional calculations, which nicely illustrates the significant challenges that LCuO 2 systems can pose for computation. In the case of compound 3, no crystal structure has been obtained, but resonance Raman data support an end-on binding mode; the electronic ground state has not been determined.…”
Section: Introductionmentioning
confidence: 99%